Large reduction in switching current driven by spin-orbit torque in W/CoFeB heterostructures with W–N interfacial layers. (November 2020) - Kim, Yong Jin; Lee, Min Hyeok; Kim, Gyu Won; Kim, Taehyun; Cha, In Ho; Nguyen, Quynh Anh T.; Rhim, Sonny H.; Kim, Young Keun
Abstract: Injecting an electrical current into a nonmagnetic layer toward the in-plane direction can reverse the magnetization direction of an adjacent ferromagnetic layer in a nonmagnet/ferromagnet heterostructure via spin-orbit torque (SOT). One of the most critical issues for memory and logic device applications is to reduce the critical current to assure low energy consumption. Herein, we report both enhanced SOT efficiency and reduced SOT-induced switching current in perpendicularly magnetized W/CoFeB heterostructures, where ultrathin tungsten nitride (W–N) layers with various N-compositions and thicknesses are placed in between W and CoFeB layers. The composition of the W–N layers affects the microstructure and, therefore, the electrical properties. The measured SOT efficiency is 0.54, and the switching current reduces to approximately one-fifth of its original value in the 0.2-nm-thick W–N layer sample containing 42 at% N. Our results suggest interface engineering is a practical approach to reduce switching current. Graphical abstract: Image, graphical abstract